Maria Sten: de literatura prehispánica mexicana al boom en Polonia - Dabrowska, Monika (Itinerarios: revista de estudios lingüisticos, literarios, históricos y antropológicos, 2023)
El artículo presenta la fi gura de la investigadora y traductora de origen polaco establecida en México, Maria Sten (1917-2007). Considera su aporte como investigadora de la UNAM, especialista en literatura mesoamericana y en teatro prehispánico y novohispano. Por otro lado, destaca su esfuerzo de popularizar la imagen de México y de su cultura en Polonia, traduciendo y editando en polaco obras literarias y publicaciones científi cas de autores mexicanos (Rosario Castellanos, Carlos Fuentes, Augusto Monterroso, Miguel León-Portilla). A su vez Sten traduce y divulga en México a autores polacos y sus obras teatrales (Stanisław Witkiewicz, Sławomir Mrożek). Su contribución al acercamiento literario entre Polonia y México se sitúa en el contexto del diálogo intercultural polaco-mexicano del siglo XX. Tras ponderar sus publicaciones, tanto en México como en Polonia, se concluye su contribución a la visión del México prehispánico y el carácter pionero de sus textos editados en Polonia en los años 60. Su trabajo preparó el terreno para el boom latinoamericano en nuestro país.
Maria Sten: from Mexican Prehispanic Literature to the Boom in Poland
The article presents the figure of Maria Sten (1917-2007), the researcher and translator of Polish origin established in Mexico. On one hand it considers her contribution as a researcher at the UNAM, and a specialist in Mesoamerican literature and in Prehispanic and Colonial theater. On the other hand, the paper emphasizes her effort to popularize the image of Mexico and its culture in Poland by translating into Polish and publishing the literary works and scientifi c publications of Mexican authors (Rosario Castellanos, Carlos Fuentes, Augusto Monterroso, Miguel Leon-Portilla). At the same time Sten translated and popularized in Mexico Polish authors and their theatrical works (Stanisław Witkiewicz, Sławomir Mrożek).The contribution of Maria Sten to the literary approach between Poland and Mexico is situated in the context of Polish-Mexican intercultural dialogue in the twentieth century. After pondering her publications, both in Mexico and in Poland, the paper concludes with presenting her contribution to the vision of pre-Columbian Mexico and the pioneering nature of her texts published in Poland in the 60s. Her work prepared the ground for the reception of the Latin American Boom in Poland.
Keywords: Maria Sten; teatro prehispánico; relaciones Polonia-México; traducción; boom literario; pre-Hispanic theater; Polish-Mexican relations; translation; Latin American Boom